Impact of Corporate Social Responsibility on Customer Loyalty: Evidence from Nepalese Insurance Companies in Kathmandu Valley (Quest Journal of Management and Social Sciences, 2026)
Background: Corporate Social Responsibility (CSR) has become a strategic tool for enhancing customer loyalty in the insurance sector. In Nepal, insurance companies increasingly adopt CSR initiatives to build ethical and trustworthy reputations. Understanding how CSR influences corporate image, reputation, and customer loyalty is crucial for sustaining competitive advantage and long-term customer relationships.Purpose: The purpose of this study is to determine the impact of CSR initiatives on customer loyalty across Nepalese insurance companies.Design/methodology /approach: This study follows a post-positivist philosophy and adopts an exploratory research design. Quantitative data from 403 insurance customers were collected using KOBO toolbox and analyzed using descriptipive and inferential statistics with MS Excel, and the Smart PLS 4.0.Findings: The research findings reveal statistically significant relationships between CSR and corporate image (CI), CSR and corporate reputation (CR), and CSR and customer loyalty (CL), and more importantly, they extend existing knowledge by confirming the mediating roles of CI and CR in the CSR–CL relationship. Empirical results show that CSR significantly influences CI (β = 0.242, p < 0.001), CR (β = 0.141, p = 0.006), and CL (β = 0.626, p < 0.001), while CI (β = 0.424, p < 0.001) and CR (β = 0.242, p = 0.001) further enhance customer loyalty.Conclusion: The study confirms significant relationships between CSR and corporate image, corporate reputation, and customer loyalty, while highlighting the mediating roles of image and reputation in the CSR–loyalty link. Nepalese insurance companies that actively engage in CSR enhance customer loyalty by being perceived as ethical, trustworthy, and value-oriented.Keywords: Corporate social responsibility, corporate image, corporate reputation, Customer Loyalty.